Dimeric, Two‐Dimensional and Metal‐Centered Rectangular Heterometallic CuII–AgI/CdII/BaII Systems Derived from a Single Compartmental Ligand. Issue 33 (3rd September 2018) - Mandal, Shuvankar; Hari, Nairita; Mondal, Suraj; Mohanta, Sasankasekhar
Abstract: The present study deals with one dimer‐of‐dinuclear type compound, [{Cu II LAg I (NO3 )}2 ] (1 ), one pentametallic and metal‐centered rectangle type compound, [Ba II (Cu II L)4 ](ClO4 )2 (2 ), and one dinuclear based two‐dimensional coordination polymer, [Cu II LCd II (μ1, 5 ‐dicyanamide)2 ]n (3 ), where H2 L=N, N′‐bis(salicylidene)‐1, 4‐butanediamine. The syntheses and crystal structures of1–3, electrospray ionization mass spectra in positive mode of1 and2 and variable‐temperature magnetic properties of2, are described. Two symmetry related diphenoxo‐bridged dinuclear Cu II Ag I moieties are interlinked in1 by Ag–π (η 2 ‐) bonds to form dimer‐of‐dinuclear type structure. One diphenoxo‐bridged dinuclear Cu II Cd II moiety is interlinked with four symmetry related dinuclear moieties by four μ1, 5 ‐dicyanamide ligands, which link Cd II centers, to generate two‐dimensional polymeric structure in3 . In the [Ba II (Cu II L)4 ] 2+ cation in2, the Ba II ion is coordinated to two μ‐phenoxo oxygen atoms of each of the four [Cu II L] fragments; the four copper(II) ions are positioned to form an approximate rectangle, i. e., the pentametallic [Ba II (Cu II L)4 ] 2+ cation in2 is a metal‐centered rectangle. ESI‐MS positive of1 and2 have been recorded and the ions in the spectra have been reasonably assigned. Variable‐temperature magnetic studies of2 reveal very weak antiferromagnetic interaction ( J =–0.14 cm –1 ) between the copper(II) ions. The structure of2 represents a new type among compounds from related ligands. Abstract : Copper(II) metallo‐ligand from N, N′‐bis(salicylidene)‐1, 4‐butanediamine is treated with AgNO3, hydrated Cd(ClO4 )2 + Nadca and hydrated Ba(ClO4 )2 to result in the formation of, respectively, dimer‐of‐dinuclear {Cu II Ag I }2, dinuclear based 2‐D Cu II Cd II n and an interesting metal‐centered rectangle or 'Larger Star' Ba II Cu II 4 .